To Study the Relationship between Intellectual Capital and Productivity in Iran Productive Industries - Mohammadreza Tabibi (مدیریت بهره وری, 2019)
Successful companies have realized that investment on intellectual capital to create valuable products and services is essential. Moreover, in unsafe situations for new investment, enterprise has no choice except optimal use of available resources, Productivity is defined as an efficient and effective use of resources for production. The importance of this research is in highlighting the role of intellectual capital in the productivity of materials and chemical products industry. Firstly, in this study the value of intellectual capital investment companies based on the method applied and also the value of productivity based on productivity indicators presented by national Iranian productivity organization for a period of 10 years from 1379 to 1388 calculated and next the relationship between intellectual capital and the productivity of investment companies in Tehran stock exchange of material and chemical products has been assessed. The statistical method used to analyze data is GLS. General purpose of this study is to examine the relationship between intellectual capital and company productivity. The important finding of this research is a positive relation between human capital efficiency and labor productivity.